2016
DOI: 10.1136/jnnp-2015-311952
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale multicentre cerebral diffusion tensor imaging study in amyotrophic lateral sclerosis

Abstract: ObjectiveDamage to the cerebral tissue structural connectivity associated with amyotrophic lateral sclerosis (ALS), which extends beyond the motor pathways, can be visualised by diffusion tensor imaging (DTI). The effective translation of DTI metrics as biomarker requires its application across multiple MRI scanners and patient cohorts. A multicentre study was undertaken to assess structural connectivity in ALS within a large sample size.Methods442 DTI data sets from patients with ALS (N=253) and controls (N=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(169 citation statements)
references
References 50 publications
9
160
0
Order By: Relevance
“…1) [14,19]. Naturally, the duration and transition of each stage cannot be determined within the context of post-mortem cross-sectional studies; nevertheless, in vivo diffusion-tensor imaging (DTI) and diffusion-weighted imaging (DWI)-based results gained from ALS patients fit in well with the proposed hypothetical sequence of neuropathological staging [20][21][22][23][24]. stage 1: Abnormal changes develop not only in Betz pyramidal cells in the deep layer Vb of the primary motor cortex (Brodmann field 4) [25] but also in lower brainstem and spinal cord α-motor neurons (▶Fig.…”
Section: The Transmission Of the Pathology From Cortical Pyramidal Cementioning
confidence: 94%
“…1) [14,19]. Naturally, the duration and transition of each stage cannot be determined within the context of post-mortem cross-sectional studies; nevertheless, in vivo diffusion-tensor imaging (DTI) and diffusion-weighted imaging (DWI)-based results gained from ALS patients fit in well with the proposed hypothetical sequence of neuropathological staging [20][21][22][23][24]. stage 1: Abnormal changes develop not only in Betz pyramidal cells in the deep layer Vb of the primary motor cortex (Brodmann field 4) [25] but also in lower brainstem and spinal cord α-motor neurons (▶Fig.…”
Section: The Transmission Of the Pathology From Cortical Pyramidal Cementioning
confidence: 94%
“…The results provided by TST were shown to correlate to those provided by DTI [46], but the TST was found to be frankly more sensitive in the detection of UMN involvement in ALS patients [43]. However, a recent multicentre study showed that the reliability of DTI tractography might improve in terms of specificity and sensitivity in the diagnosis of ALS, but on condition of using complex processing and analysis methods [69]. Thus, the real value of this technique in the individual diagnosis of ALS remains to be determined in daily practice.…”
Section: Motor Evoked Potentialsmentioning
confidence: 85%
“…Despite all this clinical and etiopathogenic complexity, some faces of ALS, including FTD-MND continnum, have been elucidated by magnetic resonance imaging (MRI) techniques, which have proved to be useful to reveal microstructural brain abnormalities associated with different rates of symptom progression 6,7 . A plausible biomarker for upper motor neuron degeneration in ALS is becoming tangible after recent advances in high-throughput MRI techniques, through which one can believe that we are going to the forefront of a breakthrough able to translate research findings into reliable clinical tests that will support the practice of personalized medicine 8,9,10 .…”
mentioning
confidence: 99%